Christian Spiritual Experience as a Model of a Culture of Dialogue - Rybicki Adam (Journal for Perspectives of Economic Political and Social Integration, 2016)
A space for dialogue between people and the cultures is a focus of this article. To start with, the biblical basis for analysing spiritual experience is presented, followed by the components of Christian spiritual-religious experience. It is also explored whether it is possible to cross-reference the said components with the culture of dialogue. A particular focus is made on the spirituality of encounter and mysticism that leads to a conclusion that a reliable and continuously deepening reflection on Christian spirituality shows its value not only on a “vertical” (upright) plane, i.e. a dialogue with God, but also on a horizontal, flat plane. It shapes the overall attitude of a person, both towards other people and towards themselves, as well as towards the world around them. Certain elements may play a major role in shaping the culture of dialogue between people and the communities of people. These elements are: relational character, desire of getting to know “the other you”, emphasizing the dignity of “the other you”, mutual respect, shared search for and acceptance of the truth and a communal dimension (communion). The ethical aspects of spiritual experience – including a mystical experience – such as conscience, virtue or value, have also been regarded because the ethical elements play a very important role in the dialogue of people and communities.